KEWENANGAN PERADILAN MENGADILI TERHADAP SENGKETA AKTA PEJABAT PEMBUAT AKTA TANAH DAN BALIK NAMA PADA SERTIPIKAT BERDASARKAN HIBAH HAK ATAS TANAH YANG CACAT HUKUM - Deasy Willyza (Universitas Sriwijaya, 2015)
Abstract : The Background of the writing is the result of Palembang District Court No.62/PDT.G/2010/PN PLG juncto High Court verdict Palembang 101/PDT/2011/PT.PLG Number, Object lawsuit is Grant Deed No. 623/2009 dated July 30, 2009 which made before a Land Deed Official TA, SH. The decision of the judges in a lawsuit in state court can not be accepted and the decision of the judge also rejected the appeal in its entirety , a lawsuit can not be accepted because of the competence of courts to sue the Land Deed Officer and Head of the Land Office should at the State Administrative Court is not in Judicial Affairs , while the Grant Deed to cancel Judicial Affairs is the authority for Deed Land Deed Official beschikking not the result of a decision , but based on the wishes of the parties ( Partij acte ) contractual and to cancel the certificate that has been turned over the name of the authority of the State Administrative Court . Legal sanctions for Land Deed Official TA , SH which has made the Deed of Grant No. 623/2009 dated July 30, 2009 which can be legally flawed administrative sanctions and dismissal with no respect from his post by the National Land Agency of the Republic of Indonesia , after a court ruling have permanent legal force . While the legal sanctions for the Head of the Land Office had registered under the name of the Certificate of Property No. 910/24 downstream Village by the Deed of Grant No. 623/2009 which is a legal disability for severe disciplinary offense which is the Head of the Land Office for Civil Servants, the sanction under Article 7 figure 4 Government Regulation No. 53 of 2010 Concerning Civil Service Discipline, demotion level may be lower for 3 (three) years, in order to decrease the transfer of lower level positions, exemption from office, dismissal with respect not by his own request as Employee Civil, and dismissal with no respect as a civil servant. Keywords: the Judicial Authority of judging, registration of transfer of rights of Evidence, Sanctions Law Land Deed Officer and Head of the Land Office